Examining potential threats of eavesdropping in TCP stream of personal interactive transmission session - Abubakar Ibrahim, Adamu; Muhammed Najmuddin, Nadhirah; Mohd Alwi, Rabiatul Adawiyah; Mohamad Faizal, Nur Amirotul Izzah (IIUM Press, 2024)
This study establishes that Personal Interactive Transmission Sessions conducted using TCP streams provide exceptional convenience and immediacy. However, they also provide noteworthy challenges and considerations, especially in terms of security, integrity, and performance. This study investigates the security weaknesses present in potential eavesdropping threats on TCP Streams during personal interactive transmission sessions. An experimental analysis was carried out,by doing a comprehensive analysis of network traffic using Wireshark. The investigation reveals a notable vulnerability in the management of user-provided data, together with the possible risks of eavesdropping, emphasizing the urgent need for enhanced security measures. The findings underscore the need of proactive cybersecurity strategies, such as frequent security audits, vulnerability assessments, and the implementation of robust encryption methods, to safeguarduser privacy and ensure data integrity. To enhance risk mitigation, data protection, and user confidence in the digital environment, organizations should prioritize addressing potential eavesdropping threats during transmission sessions that involve sensitive personal data.